2018
DOI: 10.2147/idr.s170952
|View full text |Cite
|
Sign up to set email alerts
|

Widespread amphotericin B-resistant strains of <em>Aspergillus fumigatus</em> in Hamilton, Canada

Abstract: PurposeAmphotericin B (AMB) is one of the major antifungal drugs used in the management of aspergillosis and is especially recommended for treating triazole-resistant strains of Aspergillus fumigatus. However, relatively little is known about the AMB susceptibility patterns of A. fumigatus in many parts of the world. This study aims to describe the AMB susceptibility patterns in Hamilton, Ontario, Canada.MethodsThe in vitro susceptibilities of 195 environmental and clinical A. fumigatus isolates to AMB were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
0
30
1
3
Order By: Relevance
“…To date, no resistance problems associated with echinocandins and amphotericin B have been identified in clinics. However, echinocandin-resistant mutants can be induced easily in vitro (630,631), and hot spots for point mutations inducing the resistance to amphotericin were identified in A. fumigatus after use of natamycin (632)(633)(634) and are starting to be seen in laboratories (635,636). However, resistance to AMB is only anecdotal.…”
Section: Antifungal Drugs and Therapy Antifungal Drugs And Associatedmentioning
confidence: 99%
“…To date, no resistance problems associated with echinocandins and amphotericin B have been identified in clinics. However, echinocandin-resistant mutants can be induced easily in vitro (630,631), and hot spots for point mutations inducing the resistance to amphotericin were identified in A. fumigatus after use of natamycin (632)(633)(634) and are starting to be seen in laboratories (635,636). However, resistance to AMB is only anecdotal.…”
Section: Antifungal Drugs and Therapy Antifungal Drugs And Associatedmentioning
confidence: 99%
“…Since its emergence in 1997, resistance to triazole in A. fumigatus has steadily increased and is a current global health menace [ 46 , 47 ]. Furthermore, in A. fumigatus, there are emerging reports of increased resistance to polyenes such as amphotericin B (AMB), an antifungal to which very little resistance has been reported thus far [ 48 , 49 ]. For example, a recent study carried out in Brazil showed that 27% of a clinical sample of A. fumigatus isolates was resistant to AMB (minimum inhibitory concentration (MIC) > 2 mg/L) [ 48 ].…”
Section: The Genus Aspergillusmentioning
confidence: 99%
“…Interestingly the killing mode of antifungal drugs in C. elegans model was different from that in the in vitro culture. The macrolide polyene AmB is a well-known broad-spectrum fungicidal agent (Hamill, 2013 ; Ashu et al, 2018 ) while azole drugs, i.e., VoZ and ItrZ, are mainly fungistatic against A. fumigatus (Meletiadis et al, 2007 ). However, visible hyphal filamentation from a number of infected worms graduated to “ghost stage” under AmB treatment whereas only diffused internal hyphal growth and early germinated conidia were observed from worms treated with VoZ and ItrZ ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of drug resistant strains to the wide range of currently available drugs has posed a serious challenge as cases are rising globally (Prigitano et al, 2017 , 2019 ; Abdolrasouli et al, 2018 ). Reports of A. fumigatus resistance to azole drugs (Hagiwara et al, 2017 ; Sharma et al, 2019 ), polyene drugs such as amphotericin B (Ashu et al, 2018 ), and echinocandin drugs (Beer et al, 2018 ) are increasing in both clinical (Prigitano et al, 2017 ; Abdolrasouli et al, 2018 ; Hagiwara et al, 2018 ) and environmental isolates (Vaezi et al, 2018 ; Prigitano et al, 2019 ). With the limited repertoire of antifungal drug classes, there is therefore the need to urgently discover new therapeutic option for this infection.…”
Section: Introductionmentioning
confidence: 99%